2022
DOI: 10.1002/adma.202206478
|View full text |Cite
|
Sign up to set email alerts
|

Nature‐Inspired Design of Molybdenum–Selenium Dual‐Single‐Atom Electrocatalysts for CO2 Reduction

Abstract: Electrochemical CO2 reduction (ECR) is becoming an increasingly important technology for achieving carbon neutrality. Inspired by the structure of naturally occurring Mo‐dependent enzymes capable of activating CO2, a heteronuclear Mo–Se dual‐single‐atom electrocatalyst (MoSA–SeSA) for ECR into CO with a Faradaic efficiency of above 90% over a broad potential window from −0.4 to −1.0 V versus reversible hydrogen electrode is demonstrated here. Both operando characterization and theoretical simulation results ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…Chen and co-workers recently demonstrated a Mo–Se dual single-atom electrocatalyst (MoSA–SeSA) for the CO 2 RR producing CO at a wide potential of −0.4 to −1.0 V with a FE of >90%. 37 As is presented in Fig. 4C, MoSA was proved to be the active site here since it could interact with CO 2 and its intermediates during the CO 2 RR, while SeSA could promote the performance of MoSA.…”
Section: Emerging Multicomponent Catalystsmentioning
confidence: 80%
See 1 more Smart Citation
“…Chen and co-workers recently demonstrated a Mo–Se dual single-atom electrocatalyst (MoSA–SeSA) for the CO 2 RR producing CO at a wide potential of −0.4 to −1.0 V with a FE of >90%. 37 As is presented in Fig. 4C, MoSA was proved to be the active site here since it could interact with CO 2 and its intermediates during the CO 2 RR, while SeSA could promote the performance of MoSA.…”
Section: Emerging Multicomponent Catalystsmentioning
confidence: 80%
“…The Zhai group also reported a tangible superlattice (Figure 4B producing CO at a wild potential of -0.4 to -1.0 V with a FE of > 90%. 37 As is presented in Figure 4C, MoSA was proved to be the active site here since it could interact with CO 2 and its intermediates during CO 2 RR, while the SeSA could promote the performance of MoSA. Operando and theoretical studies revealed that SeSA could tune the electronic structure via long-range electro-delocalization, which is essential to avoid the inhibition of MoSA caused by the strong CO absorption.…”
Section: Applications In Electrochemical Reactionsmentioning
confidence: 83%
“…Future work on quantifying grain sizes and density may provide additional insights into how to tune the structure of Cu nanograins for more effective C–C coupling reactions. This study points out the need for operando methods to investigate active sites of electrocatalysts instead of relying on conventional ex situ methods, especially for highly reactive Cu nanocatalysts. We would also like to point out several future directions that are required to make operando EC-STEM more accessible to the broad energy materials community. Quantification of applied potentials . A rigorous calibration of the potential of the Pt pseudo-RE in different electrolyte environments will be instrumental to benchmark electrochemistry in operando EC-STEM.…”
Section: Resultsmentioning
confidence: 97%
“…Operando attenuated total reflection surface-enhanced infrared absorption spectroscopy (ATR-SEIRAS) identifies the specific reactions of single atoms with intermediates by probing the thermodynamic forces on an atom dynamic of the intermediates. Chen and coauthors synthesized Mo–Se dual-atom catalysts on hollow nanosheets, which exhibited up to 90% FE CO under continuous electrolysis for 23 h at −0.4 to −0.8 V (Figure a) . It was observed by operando ATR-SEIRAS that the valence bands of *COOH and CO 2 of Mo single atoms fade away from −0.1 to 0 V, and the *CO valence band exists as a potential backward, indicating the strong adsorption of CO and the possibility of CO poisoning by Mo single atoms.…”
Section: Site Structure and Reaction Mechanismmentioning
confidence: 99%
“…and coauthors synthesized Mo−Se dual-atom catalysts on hollow nanosheets, which exhibited up to 90% FE CO under continuous electrolysis for 23 h at −0.4 to −0.8 V (Figure6a) 107. It was observed by operando ATR-SEIRAS that the valence bands of *COOH and CO 2 of Mo single atoms fade away from −0.1 to 0 V, and the *CO valence band exists as a potential backward, indicating the strong adsorption of CO and the possibility of CO poisoning by Mo single atoms.…”
mentioning
confidence: 99%